Communication and Organisational Effectiveness in Selected Public Universities in Uganda - Turyahikayo, Wilberforce; Mugizi, Wilson (Journal of Research in Education and Pedagogy, 2025)
Organisational effectiveness is critical for universities as it enhances stakeholder satisfaction, improves employee relations, streamlines business processes, promotes learning and development, and contributes to overall institutional success. However, achieving organisational effectiveness has remained a significant challenge for public universities in Uganda. This study examined the influence of communication on organisational effectiveness, focusing on how communication structure, flow, climate, and message characteristics influenced organisational effectiveness. The study adopted the quantitative approach; hence, a correlational research design was employed in this study. The study focused on a sample of 231 university managers, which included a diverse group of both academic and administrative leaders from four public universities in Uganda. The carefully selected study participants represented the various levels of management within the institutions, ensuring a comprehensive perspective on the role of communication in organisational effectiveness. The data were gathered using self-administered questionnaires capturing detailed information on various aspects of communication, including structure, flow, climate, and message characteristics, and organisational effectiveness in terms of productivity, adaptability, and flexibility. The findings from the descriptive analysis revealed that while organisational effectiveness was moderate, communication levels were high. The PLS-SEM results showed that communication structure, flow, and climate had a significant positive effect on organisational effectiveness. The study concluded that a well-defined communication structure is essential for effective organisational effectiveness, effective communication flow involving smooth information exchange is crucial for organisational effectiveness, and an organisational climate that fosters effective information exchange is essential for organizational effectiveness. Therefore, university managers should focus on creating a clear communication structure, ensuring the smooth flow of information, and cultivating a conducive communication climate to promote organisational effectiveness. The implication of this study is that it underscores the importance of a well-defined communication structure, effective communication flow, and positive communication climate as essential components that can significantly enhance organisational effectiveness in universities.